Focus of Clinical Supervision in Integrated Behavioral Health (IBH) Settings - Yeşim Giresunlu; Zahide Sunal; Gulsah Kemer (Teaching and Supervision in Counseling, 2025)
We explored 18 mental health counselor trainees’ (MHCT) experiences regarding the focus of supervision they received in Integrated Behavioral Health settings. Utilizing Q methodology, we obtained Clinical Skill Development as a Counselor and Interdisciplinary Team Membership as the main areas of trainees’ supervision focus. More specifically, counselor trainees identified developing clinical skills related to client care, case conceptualization, and the delivery of clinical services, as well as strengthening their professional identity while integrating into an interdisciplinary team, as critical areas of their supervision. We discussed the findings along with practical and research implications as well as limitations of the study.
Keywords: Integrated Behavioral Health (IBH); counseling supervision; supervision focus; Q methodology; Mental Health Counselor Trainee